How to do this question?

PKS Matematika Wajib Kelas XI SMA/MA

2 Answers
Jun 27, 2018

Option D

Explanation:

Take any pair:

1/(sqrtn-1) - 1/(sqrtn+1)1n11n+1

= (sqrtn + 1 - sqrtn +1)/((sqrtn-1)(sqrtn+1))=n+1n+1(n1)(n+1)

= (2 )/(n-1)=2n1

So, term by term:

{(n = 2, 2/1),(n=3, 2/2), (...,...),(n=20, 2/19) :}

So you have:

2/1 + 2/2 + ... + 2/19 = sum_(n=1)^19 2/n

Jun 27, 2018

Option D. See process below

Explanation:

We notice that

1/(sqrt2-1)=(sqrt2+1)/(2-1)=(sqrt2+1)/1
1/(sqrt2+1)=(sqrt2-1)/(2-1)=(sqrt2-1)/1

The sum of both expresions (the two first sum terms) is 2

1/(sqrt3-1)=(sqrt3+1)/(3-1)=(sqrt3+1)/2
1/(sqrt3+1)=(sqrt3-1)/(3-1)=(sqrt3-1)/2

The sum of both expresions (third and fourth) is 1

1/(sqrt4-1)=(sqrt4+1)/(4-1)=(sqrt4+1)/3
1/(sqrt4+1)=(sqrt4-1)/(4-1)=(sqrt4-1)/3

The sum of both terms is 2/3

For last two terms

1/(sqrt20-1)=(sqrt20+1)/(20-1)=(sqrt20+1)/19
1/(sqrt20+1)=(sqrt20-1)/(20-1)=(sqrt20-1)/19

The sum of both terms is 2/19

So we have

2+1+2/3+...+2/19=sum_(n=1)^(n=19)2/n

Correct answer: D